Development of a behavioural intervention for cognitive fatigability in multiple sclerosis: Protocol for a pilot and feasibility study - Walker, Lisa A. S.; Berard, Jason A.; Islam, Tamanna; Pilutti, Lara A.; Morrow, Sarah A.; Finlayson, Marcia (Frontiers in Rehabilitation Sciences, 2022)
Background: Up to 90% of people with multiple sclerosis (PwMS) report fatigue as one of their worst symptoms. Fatigability is an objectively measured component of fatigue. Cognitive fatigability (CF) is a breakdown in task performance following sustained cognitive effort. There is a paucity of interventions targeting CF in MS. The prior success of behavioural interventions at improving subjective fatigue suggests that adaptation of these methods may yield similar results in CF. Given the relationship between CF, sleep quality, and mood a behavioural intervention targeting these factors, such as cognitive behavioural therapy (CBT), is warranted. Given the multidimensional nature of fatigue, a multifaceted approach targeting lifestyle factors and coping (e.g., fatigue management education supplemented by CBT for insomnia and exercise) might prove efficacious. Aim: We describe a protocol for a pilot feasibility study to design and implement a multi-dimensional behavioural intervention to improve CF in PwMS. Methods: Stage 1: development of a multi-dimensional group-based videoconference-delivered behavioural intervention based on a previously successful fatigue management program for PwMS. A facilitator manual will be prepared. Course material will focus on four themes: body (sleep and physical activity), mood (impact of depression and anxiety), mind (cognitive contributions), and context (pacing, communication). Stage 2: a needs assessment survey will be completed by 100 PwMS for input on what factors are important contributors to their CF. Required modifications will be made to the course material and manual. Stage 3: the facilitator-delivered intervention will include 20 PwMS. After baseline assessment, participants will attend weekly 70-minute videoconference group sessions for 8 weeks, including homework assignments. Follow-up assessment will evaluate outcomes. Stage 4: analysis and dissemination of results. The primary outcome is improvement in CF. Additional feasibility outcomes will determine if a randomized control trial (RCT) is pursued. Stage 5: refine the intervention based on outcomes and feedback from participants. Determining which aspects participants felt were most effective will help design an RCT. Conclusion: The long-term goal is to ensure that PwMS have access to effective interventions in real-world settings to improve quality of life and enhance their ability to participate in cognitively demanding activities they enjoy.